Computationally sound mechanized proofs for Diffie-Hellman key exchange protocols - FENG Chao; ZHANG Quan; TANG Chao-jing (Tongxin xuebao)
A computationally observational equivalence model for the Diffe-Hellman key agreement primitive was pro-posed and the soundness of the model was proved.Compared with prior works,this model can extend the power of the mechanized prover CryptoVerif directly.When applying the model to proving the public-key Kerberos,the deficiency of the adversary’s capability was uncovered and an enhanced model for the adversary was presented.The model was vali-dated by verifying the public-key Kerberos in Diffie-Hellman mode with CryptoVerif automatically.Being different from current approaches,the verification procedure is both automatic and computationally sound.